2011
DOI: 10.1177/1350650111409825
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diesel contaminants on tribological performance on sliding steel on steel contacts

Abstract: This article presents the findings from a parametric study examining the effect of four contaminants (soot, oxidation, moisture, and sulphuric acid) at varying levels (four for each). It was observed that all contaminants and contaminant levels reduce the conductivity of the oil. Oxidation and soot contaminants produced large increases in viscosity. The wear rate was mainly influenced by acid and soot additions, while the coefficient of friction was increased by all contaminants and contaminant levels. The ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 55 publications
2
15
1
Order By: Relevance
“…These results suggest that the presence of CB in the oil will not necessarily cause severe wear during the tribological tests due to abrasion or mechanical action. Thus, the results presented in this study contradict the concept that suggests abrasion-induced wear is the main mechanism [13,15,17,18,53].…”
Section: Accepted Manuscriptcontrasting
confidence: 97%
See 1 more Smart Citation
“…These results suggest that the presence of CB in the oil will not necessarily cause severe wear during the tribological tests due to abrasion or mechanical action. Thus, the results presented in this study contradict the concept that suggests abrasion-induced wear is the main mechanism [13,15,17,18,53].…”
Section: Accepted Manuscriptcontrasting
confidence: 97%
“…That is to say although in both tests 1wt% CB was present in oil, the wear behaviour was different. Many studies [13,15,17,18,53] have reported that the increase in wear by soot was related to the abrasive nature of soot. The results presented in this study demonstrated that the tests which were conducted with the same levels of CB particles (1wt%) showed different levels of wear.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, abrasive wear was observed on the worn surface. Because BDS can fill the friction pairs and act as a balling bearing, the aggregation of BDS can cause abrasive wear [38,39]. Apart from the spacing and ball bearing effect, the carbon onion-like nanoparticles (NA-BDS-OLA) possibly alleviated the friction shearing through their exfoliating behavior [40], which is in accordance with the results shown in Figure 10.…”
Section: Resultssupporting
confidence: 64%
“…The post-test analysis indicates that the steel pins are susceptible to corrosive wear and pitting, both of which are tribochemical in nature, which conceivably would increase the charge observed, as tribochemical reactions involve ionic (charged) species. 16…”
Section: Resultsmentioning
confidence: 99%